Selective ablation of thymic and peripheral Foxp3+ regulatory T cell development - Yilmazer, Acelya; Zevla, Dimitra Maria; Malmkvist, Rikke; Rodríguez, Carlos Alejandro Bello; Undurraga, Pablo; Kirgin, Emre; Boernert, Marie; Voehringer, David; Kershaw, Olivia; Schlenner, Susan; Kretschmer, Karsten (Frontiers in Immunology, 2023)
Foxp3+ Treg cells of thymic (tTreg) and peripheral (pTreg) developmental origin are thought to synergistically act to ensure immune homeostasis, with self-reactive tTreg cells primarily constraining autoimmune responses. Here we exploited a Foxp3-dependent reporter with thymus-specific GFP/Cre activity to selectively ablate either tTreg (∆tTreg) or pTreg (∆pTreg) cell development, while sparing the respective sister populations. We found that, in contrast to the tTreg cell behavior in ∆pTreg mice, pTreg cells acquired a highly activated suppressor phenotype and replenished the Treg cell pool of ∆tTreg mice on a non-autoimmune C57BL/6 background. Despite the absence of tTreg cells, pTreg cells prevented early mortality and fatal autoimmunity commonly observed in Foxp3-deficient models of complete Treg cell deficiency, and largely maintained immune tolerance even as the ∆tTreg mice aged. However, only two generations of backcrossing to the autoimmune-prone non-obese diabetic (NOD) background were sufficient to cause severe disease lethality associated with different, partially overlapping patterns of organ-specific autoimmunity. This included a particularly severe form of autoimmune diabetes characterized by an early onset and abrogation of the sex bias usually observed in the NOD mouse model of human type 1 diabetes. Genetic association studies further allowed us to define a small set of autoimmune risk loci sufficient to promote beta cell autoimmunity, including genes known to impinge on Treg cell biology. Overall, these studies show an unexpectedly high functional adaptability of pTreg cells, emphasizing their important role as mediators of bystander effects to ensure self-tolerance.